2(x-2)+46=-4x

Simple and best practice solution for 2(x-2)+46=-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-2)+46=-4x equation:


Simplifying
2(x + -2) + 46 = -4x

Reorder the terms:
2(-2 + x) + 46 = -4x
(-2 * 2 + x * 2) + 46 = -4x
(-4 + 2x) + 46 = -4x

Reorder the terms:
-4 + 46 + 2x = -4x

Combine like terms: -4 + 46 = 42
42 + 2x = -4x

Solving
42 + 2x = -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
42 + 2x + 4x = -4x + 4x

Combine like terms: 2x + 4x = 6x
42 + 6x = -4x + 4x

Combine like terms: -4x + 4x = 0
42 + 6x = 0

Add '-42' to each side of the equation.
42 + -42 + 6x = 0 + -42

Combine like terms: 42 + -42 = 0
0 + 6x = 0 + -42
6x = 0 + -42

Combine like terms: 0 + -42 = -42
6x = -42

Divide each side by '6'.
x = -7

Simplifying
x = -7

See similar equations:

| 3x+8=4x-22 | | 3(x-4)-14=2(x-7)+7 | | 3x+5y+11=4(5x-2y) | | 2x^2-3x=40 | | 13x=6x+42 | | x^6+x^2= | | 4x^2+5=20 | | x+(x+6)+2x=94 | | 6n+3=63 | | 5(3y-1)-1(2y)=10 | | x^2-37=0 | | -5x^2+10x=0 | | -3+n=-91 | | -2x=7y-19 | | -17=63+n | | 2+5*3+4= | | 35x^2+x-6=0 | | n+(-3)=-91 | | 7.32xA=13.53+2.81xA | | 9+2(x-7)=0 | | 2x+(3x+4)=4 | | 92=6+3w | | 92=6+1/2 | | 7x-4=2x+2 | | 92=2+6w | | 0x-.99-3x=-15 | | 92=6+2w | | 2a^2=196 | | 0.4x=8 | | 315=21s | | 15x^2=-3-14x | | 792=-33y |

Equations solver categories